Structural tuning of galactomannan–poly(ε-caprolactone) nanocapsule hybrid hydrogels mediated by 1,2,3,4-butanetetracarboxylic acid - Jóice M. Scheibel; Laiane S. da Silva; Daniela L.T. Schmitt; Lucca S. de Avila; Lucimara M.C. Cordeiro; Melanie Gettinger; Martin Bick; Tim J. Stank; André Conceição; Yvonne Hannappel; Thomas Hellweg; Karina Paese; et al. (Carbohydrate Polymers, 2026)

Exercise-induced compensation and C-reactive protein change in adults with elevated C-reactive protein: analysis of a randomised controlled trial - James L. Dorling; John W. Apolzan; Diana M. Thomas; Christoph Höchsmann; Neil M. Johannsen; Robert Ross; Tim S. Church; Corby K. Martin (European Journal of Applied Physiology, 2026)
Purpose Exercise can reduce C-reactive protein (CRP), but heterogeneity exists and it is unclear whether exercise-induced weight compensation occurs or relates to CRP change. We examined whether compensation occurs in adults with elevated CRP during exercise and whether compensation and compensatory behaviours are associated with CRP change. Methods In this 4-month randomised controlled trial, 124 sedentary adults with elevated CRP (mean ± SD: 4.3 ± 2.5 mg/L) were randomised to a control group or a supervised aerobic exercise group expending 16 kcal/kg/week. Predicted weight change was estimated, and weight compensation (weight change – predicted weight change) was calculated. CRP was measured, and energy intake and non-exercise step count were assessed using questionnaires and pedometers, respectively. Results Weight compensation was greater in the exercise group than the control group (1.3 [95% CI, 0.6, 2.1] vs. 0.1 [95% CI, -0.6, 0.9] kg; P = 0.029). In response to exercise, compensation did not differ between participants with moderately higher (≤ 3 mg/L) and higher (> 3 mg/L) CRP ( P = 0.977). Exercisers who did not compensate exhibited a 1.2 (95% CI, 0.2, 2.2) mg/L reduction in CRP versus those who did compensate ( P = 0.016). Higher energy intake was associated with CRP change in exercisers, with each 100 kcal/day elevation in energy intake associated with a 0.1 (95% CI, 0.0, 0.2) mg/L increase in CRP ( P = 0.022). Conclusion Exercise-induced weight compensation occurs in adults with elevated CRP and is associated with attenuated improvements in CRP. Increased energy intake was associated with higher CRP in exercisers, suggesting that limiting increases in energy intake may enhance exercise-induced anti-inflammatory benefits. Clinical trials registration NCT00113061.

Site Index Trends in Pine Plantations of the Southeastern United States: Interactions with Soil and Ownership - Valentina R. Vaney; Daniel J. Johnson; Tim Martin; Geraldine Klarenberg; Jason Vogel (Journal of Forestry, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Ground truthing marine litter stranding hotspots for the Eastern Pacific Ocean coasts: A collaborative approach with school communities - Diamela De Veer; María Amenábar Cristi; Jostein Baeza Álvarez; Nicolás Battini; James T. Carlton; Camila González; Lars Gutow; Linsey Haram; Geraldine Holtmann Ahumada; Daniela Honorato Zimmer; Tim Kiessling; Ninoshka López Xalín; et al. (Journal of Environmental Management, 2026)

Demonstration of seismic monitoring of CO2 storage using a 3D acoustic laboratory - Kasper Aas Hunnestad; Robin André Rørstadbotnen; Tim-Cato Netland; Martin Landrø; Marijn Beugelsdijk; Jørgen Avdal; Børge Arntsen; Philip Ringrose; Guillaume Carraux; Anne C. Elster (International Journal of Greenhouse Gas Control, 2026)

Role of holocellulose on thermal annealing, loss of combustion reactivity and morphological changes in biomass pyrolysis - Erik Freisewinkel; Francesca Cerciello; Tim Eisenbach; David Tarlinski; Antonio Fabozzi; Martin Schiemann; Roland Span; Viktor Scherer; Osvalda Senneca (Fuel, 2026)

Neighborhood playability and early childhood development: a population-based birth cohort study - Ingrid Jarvis; Emily Gemmell; Alicia Cavanaugh; Zoë Davis; Martin Guhn; Hind Sbihi; Tim F. Oberlander; Matilda van den Bosch; Michael Brauer (Environmental Research, 2026)

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Formation-consumption neural networks for efficient chemical kinetics modeling - Felix Döppel; Tim Kircher; Martin Votsmeier (Chemical Engineering Journal, 2026)

Mountain Roads Across the Globe Significantly Alter Local Soil Thermal Microclimates - Renée Lejeune; Eduardo Fuentes‐Lillo; Jake Alexander; Romina D. Dimarco; Stef Haesen; Sylvia Haider; Lore Hostens; Anke Jentsch; Josef Kutlvašr; Jonathan Lenoir; Martin A. Nuñez; Aníbal Pauchard; et al. (Global Ecology and Biogeography, 2026)
Aim Mountain roads host plant communities that differ strongly from the adjacent natural vegetation. Besides the effect of propagule pressure, altered disturbance and soil processes, one of the reasons given for the strong influence of mountain roads on species distributions is a significantly altered soil thermal microclimate in the roadside compared to the adjacent vegetation, as a direct consequence of road disturbance. However, the thermal microclimatic differences between roadside and natural vegetation have rarely been quantified, particularly across large spatial extents. This study provides the first global quantification of roadside soil temperature patterns along elevational gradients. Location Mountain roads in eight mountain regions from the Mountain Invasion Research Network (MIREN): Argentina, Chile, Czech Republic, Norway, Spain (Tenerife and La Palma), Switzerland, and the USA. Methods In this study, we analysed in situ measured topsoil temperatures ( Results Across most regions, roadside soils exhibited consistently warmer maxima (3.62°C ± 2.61°C) and colder minima (1.39°C ± 1.40°C) than soils in adjacent vegetation. Although temperature distributions between roadside and natural habitats largely overlapped, these systematic shifts indicate increased thermal variability and higher frost risk in roadside environments. Main Conclusions Roadsides create distinct thermal microhabitats even within heterogeneous mountain landscapes. These altered temperature regimes, particularly when combined with vegetation structure and other environmental factors such as soil moisture, may influence plant performance and distribution. Our findings highlight the ecological relevance of thermal microclimates in understanding biodiversity patterns along mountain roads.

Geographic Variation in the Diet of Red Knot ( Calidris canutus ) Chicks Reflects Local Prey Communities - Reinier Blok; Mikhail K. Zhemchuzhnikov; Tim Oortwijn; Jannik Hansen; James A. Johnson; Niels Martin Schmidt; Judith D. L. van Bleijswijk; Elena Zhemchuzhnikova; Thomas K. Lameris; Jeroen Reneerkens; Tom Versluijs; Zachary M. Pohlen; et al. (Journal of Biogeography, 2026)
Aim To describe and compare the diets of an Arctic‐breeding shorebird, the Red Knot ( Calidris canutus ), across three geographically distinct breeding sites. We aimed to document the dietary patterns and identify key prey groups that characterise each population's foraging ecology. Location Northwest Alaska (Nome), Northeast Greenland (Zackenberg) and North‐Central Russia (Taimyr Peninsula). Taxon Red Knot (Aves: Calidris canutus ). Methods We characterised chick diet by applying COI DNA metabarcoding to faecal samples and quantified local prey availability using standardised arthropod pitfall trap sampling at the three Arctic breeding sites. We described and compared the dietary composition, diversity, and relative abundance of major prey taxa among locations. Results We found substantial geographical variation in the chick diet. Diptera was a major food source across all locations, but its constituent families and importance varied. In Taimyr, the diet was dominated by Tipulidae (crane flies), comprising nearly 50% of the relative read abundance (RRA). In contrast, chicks in Greenland consumed a diet dominated by Diptera (87.8%) that almost entirely lacked Tipulidae. The diet in Alaska was the most diverse, with balanced contributions from Diptera (28.5%), Coleoptera (22.3%), and Lepidoptera (23.2%), along with other invertebrate groups, including Agriolimacidae. Main Conclusions The diet of Red Knot chicks differed among the study sites and appeared to be shaped primarily by the local availability of arthropod prey. This foraging plasticity allows the species to breed successfully across a wide circumpolar range with a heterogeneous prey landscape. However, this distinct specialisation on local prey, particularly Tipulidae in Taimyr, may create a critical phenological vulnerability.

Transauricular Vagus Nerve Stimulation in Acute Ischaemic Stroke Requiring Mechanical Thrombectomy: Sham-Controlled, Randomised Device Trial - Gareth L. Ackland; David Crane; Sanjali Ahuja; Amour Patel; Tim Martin; Mareena Joseph; Onika Ottley; Rizwan Hameed; Priyanthi Dias; Salma Begum; Johannes Schroth; Russ Hewson; et al. (Translational Stroke Research, 2026)
Autonomic dysfunction leads to hemodynamic instability and immunosuppression after ischaemic stroke, and is independently associated with worse outcomes. We hypothesized that non-invasive peripheral neuromodulation, using transcutaneous auricular vagal nerve stimulation (tVNS), may reduce blood pressure variability and/or reverse immunosuppression early after ischaemic stroke requiring mechanical thrombectomy (MT). In this pre-registered phase 2 study (NCT05417009), we randomized 36 patients >18 years referred for emergent MT following an acute ischaemic stroke. Patients were randomized to receive bilateral auricular active-tVNS or sham-tVNS, for the entire MT and the morning after admission. Participants, clinicians and investigators were masked to treatment allocations. The primary outcome was systolic blood pressure variability (coefficient of variation) over the entire first 24h after mechanical thrombectomy, analysed by intention-to-treat. Secondary outcomes were whole blood RNA sequencing. Explanatory measures were time/frequency-domain measures of heart rate variability. Active-tVNS was safe in this hyperacute stroke setting, with no serious adverse events recorded. The systolic blood pressure coefficient of variability over the first 24h was 0.106±0.029 after active-tVNS, compared to 0.107±0.027 after sham-tVNS (p=0.93). Active-tVNS increased the relative expression of genes coordinating tumor-necrosis factor and toll-like receptor signaling, in parallel with alterations in heart rate variability over the first 24h after MT. This phase 2 study established thatearly tVNS is safe and feasible in the hyperacute phase of acute ischaemic stroke requiring MT, but did not alter systolic blood pressure variability. Trial registration number: NCT05417009, registered 8 TH June 2022.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Phenotypic sex determines recombination rate and distribution in sex-reversed rainbow trout (Oncorhynchus mykiss) - Cathrine Brekke; Tim Martin Knutsen (Aquaculture, 2026)

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

Microclimate vulnerability under coupled effects of changing climate and forest structure - Joanna Lumbsden-Pinto; Tim Green; Kathy Schwager; Martin Dovciak (Agricultural and Forest Meteorology, 2025)

Kidney morphological changes associated with early-life carbonaceous ultrafine particle exposure: A pathomics approach - Leen Rasking; Kenneth Vanbrabant; Peiqi Sun; Maartje Vangeneugden; Martin Strauch; Roel P.F. Schins; Flemming R. Cassee; Hannelore Bové; Katrien De Vusser; Tim S. Nawrot; Alessandra Tammaro; Peter Boor; et al. (Environmental Research, 2025)

The Importance of Landscape Composition for Pest Control and Crop Yield: A Global Quantitative Synthesis - Katja Poveda; Daniel S. Karp; Rebecca Chaplin‐Kramer; Mary Centrella; Tim Luttermoser; Ricardo Perez‐Alvarez; Megan E. O'Rourke; Emily A. Martin; Heather Grab (Ecology Letters, 2025)
Land‐use change has altered the composition of our landscapes to favour agriculture, negatively affecting biodiversity and ecosystem services. However, the links between landscape composition, pest control and yield remain unclear. Using a global structural equation model of 116 studies from 28 countries, we tested three hypotheses: the ‘natural enemy hypothesis’, that natural areas increase natural enemies and suppress pests; the ‘resource concentration hypothesis’, that more agriculture increases pests; and the ‘agronomic quality hypothesis’, that agriculture‐dominated landscapes occur in high‐yielding areas. Results show landscape composition affects yield directly and indirectly through crop, herbivore and natural enemy traits. At larger scales (~1250 m), natural habitats increase yield, but at smaller scales (~250 m), yields decline with more surrounding natural habitat, likely due to lower agronomic quality or edge effects. Our findings suggest that we can harness the positive effects of natural areas at large scales while mitigating drawbacks at smaller scales to promote sustainable production.

Garnet as a reliable timekeeper in Archean polymetamorphic terranes - Jonas Kaempf; Chris Clark; Tim E. Johnson; Mudlappa Jayananda; Martin Hand; Krishnan Sajeev (Earth and Planetary Science Letters, 2025)

Learning kinetics from non-ideal reactors by implicitly solved finite volumes and global reaction neural networks - Tim Kircher; Martin Votsmeier (Chemical Engineering Journal, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Factors influencing the abundance of European green crab Carcinus maenas: combined effects of temperature, habitat and predator release - Mikkel Steen Nielsen; Jon C. Svendsen; Tim Wilms; Jeannet L. Bertelsen; Bo Mammen Kruse; Martin Lindegren (Estuarine, Coastal and Shelf Science, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

Enabling micro-kinetics based simulation of industrial packed-bed reactors by physics-enhanced neural networks - Felix Biermann; Riccardo Uglietti; Felix A. Döppel; Tim Kircher; Mauro Bracconi; Matteo Maestri; Martin Votsmeier (Chemical Engineering Journal, 2025)

Ion mobility spectrometer with heated sample inlet - Solution to the issue of temperature effect on resolving power - Martin Lippmann; Moritz Hitzemann; Timo Sawatzki; Jonas Winkelholz; Alexander Nitschke; Tim Kobelt; Stefan Zimmermann (Analytica Chimica Acta, 2025)

Assessing marine traffic and related pressures and threats to cetacean populations to support vessel management in the Mascarene Important Marine Mammal Area - Virginie Plot; Vanessa Estrade; Julie Martin; Thomas Rostaing; Tim Collins; Violaine Dulau (Marine Policy, 2025)

Soil-moisture-atmosphere coupling hotspots and their representation in seasonal forecasts of boreal summer - Jonathan J. Day; Frederic Vitart; Tim Stockdale; Patrica de Rosnay; Constantin Ardilouze; Daniele Peano; Antonella Sanna; Kristina Fröhlich; Martin Andrews (Climate Dynamics, 2025)
This study examines soil-moisture-atmosphere coupling “hotspots” across the Northern Hemisphere during the summer months and evaluates their representation in seasonal forecasting systems. Using hindcasts from the Copernicus Climate Change Service (C3S) multi-model seasonal forecast ensemble, the analysis explores the predictability of land–atmosphere interactions related to soil moisture anomalies. The results indicate that regions with strong soil-moisture-atmosphere coupling, such as parts of western North America, southern Europe, and Central Asia, exhibit potential for predicting seasonal temperature and precipitation patterns a season or more in advance. However, significant uncertainty exists in estimates of the soil-moisture initial conditions and soil-moisture persistence timescales. Moreover, while some regions exhibit realistic coupled behaviour, others, including a large swathe of North America, Eastern Europe, and Northern India display exaggerated coupling, resulting in systematic errors in temperature forecasts. This study underscores the potential for predicting the atmosphere in summer based on memory of soil-moisture initial conditions whilst highlighting the need to improve the representation of soil-moisture atmosphere feedbacks in order to enhance the skill of seasonal climate predictions over land.

Distributed acoustic sensing (DAS) for longwall coal mines - Derrick Chambers; Alexander Ankamah; Ahmad Tourei; Eileen R. Martin; Tim Dean; Jeffery Shragge; John A. Hole; Rafal Czarny; Gareth Goldswain; Jako du Toit; M. Shawn Boltz; James McGuiness (International Journal of Rock Mechanics and Mining Sciences, 2025)

Validation of GEMS operational v2.0 total column NO2 and HCHO during the GMAP/SIJAQ campaign - Kangho Bae; Chang-Keun Song; Michel Van Roozendael; Andreas Richter; Thomas Wagner; Alexis Merlaud; Gaia Pinardi; Martina M. Friedrich; Caroline Fayt; Ermioni Dimitropoulou; Kezia Lange; Tim Bösch; et al. (Science of The Total Environment, 2025)

Characterization of native starch granules from different botanical sources and the contribution of surface-associated lipids and proteins to the accuracy of 3D food printing - Martin Philipp Heckl; Tim Kratky; Mario Jekle; Thekla Alpers; Thomas Becker (Journal of Food Engineering, 2025)

A cold but stable 4,200 yr event in Britain and the northeastern Atlantic region - Ian Candy; Laura Boyall; Paul Lincoln; Celia Martin-Puertas; Ian Matthews; Tim Holt-Wilson; Jose Valcarcel (Quaternary Science Reviews, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Temporal variability of litter pollution of rivers in Germany – A long-term assessment by schoolchildren as citizen scientists - Sinja Dittmann; Tim Kiessling; Katrin Knickmeier; Janto Schönberg; Dennis Brennecke; Mandy Hinzmann; Doris Knoblauch; Martin Thiel (Marine Pollution Bulletin, 2024)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Seabirds as biovectors in the transport of plastic debris across ecosystem borders: A case study from the Humboldt Current Upwelling System - Claudia E. Fernández; Guillermo Luna-Jorquera; Verónica González Encinas; Andrea Auger Lancelloti; Carlos Lantadilla; Roberto Aguilar-Pulido; Tim Kiessling; Katrin Knickmeier; Andrea I. Varela; Martin Thiel (Science of The Total Environment, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Serious gaming as potential training tool for recognition of adverse drug reactions: side-effect exposure—medical education (SeeMe) - Ingmar Bergs; Laura Bell; Sebastian Fedrowitz; Tim Krüger; Martin Lemos; Julia C. Stingl; Katja S. Just (European Journal of Clinical Pharmacology, 2024)
Purpose The recognition of adverse drug reactions (ADRs) is an important part of daily clinical work. However, medical education in this field is mostly drug-based and does not address adequately the complexity of this field regarding individual risk factors and polypharmacy. This study investigates the potential of the web-based serious game SeeMe (side-effect exposure—medical education) in pharmacological education of medical students to improve the recognition of relevant ADRs. Methods One hundred fifty-seven medical students were recruited to evaluate the serious game SeeMe . SeeMe was developed to improve knowledge and recognition of ADRs in clinical practice. Players take on the role of a physician trying to understand fictional patients with ADRs. Before and after an 8-week playing period, an evaluation was carried out through a pre- and post-questionnaire and a pre- and post- knowledge test. Results The students achieved significantly better results in the knowledge test, as almost twice as many exam-relevant questions were answered correctly ( p < 0.001). The serious game had a positive effect on the students’ perception of the importance of ADRs. Conclusion This study demonstrates the potential of web- and case-based fictional serious games in medical education. The improved recognition of side effects represents a crucial step for education and training in clinical pharmacology. Future versions of the serious game may take this further and focus on training in the treatment of ADRs and their relevance in various healthcare professions.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

From ice-dammed lake to aeolian dunes in the Store Mosse area, SW Sweden - Helena Alexanderson; E. Martin Lund; Tim Bjermo (Quaternary Geochronology, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Detection of Coxiella burnetii in the mammary gland of a dairy goat - Benjamin Ulrich Bauer; Martin Peters; T. Louise Herms; Martin Runge; Peter Wohlsein; Tim K. Jensen; Martin Ganter (Veterinary Research Communications, 2024)
The zoonotic bacterium Coxiella (C.) burnetii can be excreted by infected goats through birth products and milk. The detection of C. burnetii DNA in the mammary gland tissue of infected dairy goats and intermittent milk shedders has been reported, but confirmation of C. burnetii bacteria in the udder remained pending. The pathogen caused abortions in a 152-head dairy goat herd, resulting in the vaccination against C. burnetii of the entire herd with annual boosters. To monitor the C. burnetii shedding at herd level, monthly bulk tank milk (BTM) samples were analyzed using PCR (IS 1111 ). Despite vaccination, C. burnetii DNA was detected in BTM samples within the first 16 months of the study. Therefore, individual milk samples were tested on four different occasions several months apart to identify potential intermittent milk shedders. Only one goat (#67455) tested positive three times. This goat was necropsied to investigate the presence of C. burnetii in the udder and other organs. PCR detected C. burnetii DNA solely in both mammary glands and the left teat cistern. Immunohistological examination identified C. burnetii antigen in mammary gland tissue, confirmed by the detection of C. burnetii bacteria in the mammary epithelial cells using fluorescence in situ hybridization. The removal of goat #67455 led to negative BTM samples until the end of the study. The findings demonstrate the occurrence of C. burnetii in the mammary gland of a naturally infected and vaccinated goat. The presence possibly contributed to intermittent milk shedding of goat #67455, and the mammary gland tissue may serve as a replicative niche for C. burnetii .

Cross-scale and integrative prioritization of multi-functionality in large river floodplains - Martin Tschikof; Barbara Stammel; Gabriele Weigelhofer; Elisabeth Bondar-Kunze; Gabriela Costea; Martin Pusch; Zorica Srdević; Pavel Benka; David Bela Vizi; Tim Borgs; Thomas Hein (Journal of Environmental Management, 2024)

Divergent agricultural development pathways across farm and landscape scales in Europe: Implications for sustainability and farmer satisfaction - Julian Helfenstein; Samuel Hepner; Amelie Kreuzer; Gregor Achermann; Tim Williams; Matthias Bürgi; Niels Debonne; Thymios Dimopoulos; Vasco Diogo; Wendy Fjellstad; Maria Garcia-Martin; Józef Hernik; et al. (Global Environmental Change, 2024)

Deep learning–assisted biodiversity assessment in deep-sea benthic megafauna communities: a case study in the context of polymetallic nodule mining - Daphne Cuvelier; Martin Zurowietz; Tim W. Nattkemper (Frontiers in Marine Science, 2024)
Introduction Technological developments have facilitated the collection of large amounts of imagery from isolated deep-sea ecosystems such as abyssal nodule fields. Application of imagery as a monitoring tool in these areas of interest for deep-sea exploitation is extremely valuable. However, in order to collect a comprehensive number of species observations, thousands of images need to be analysed, especially if a high diversity is combined with low abundances such is the case in the abyssal nodule fields. As the visual interpretation of large volumes of imagery and the manual extraction of quantitative information is time-consuming and error-prone, computational detection tools may play a key role to lessen this burden. Yet, there is still no established workflow for efficient marine image analysis using deep learning–based computer vision systems for the task of fauna detection and classification. Methods In this case study, a dataset of 2100 images from the deep-sea polymetallic nodule fields of the eastern Clarion-Clipperton Fracture zone from the SO268 expedition (2019) was selected to investigate the potential of machine learning–assisted marine image annotation workflows. The Machine Learning Assisted Image Annotation method (MAIA), provided by the BIIGLE system, was applied to different set-ups trained with manually annotated fauna data. The results computed with the different set-ups were compared to those obtained by trained marine biologists regarding accuracy (i.e. recall and precision) and time. Results Our results show that MAIA can be applied for a general object (i.e. species) detection with satisfactory accuracy (90.1% recall and 13.4% precision), when considered as one intermediate step in a comprehensive annotation workflow. We also investigated the performance for different volumes of training data, MAIA performance tuned for individual morphological groups and the impact of sediment coverage in the training data. Discussion We conclude that: a) steps must be taken to enable computer vision scientists to access more image data from the CCZ to improve the system’s performance and b) computational species detection in combination with a posteriori filtering by marine biologists has a higher efficiency than fully manual analyses.

Global reaction neural networks with embedded stoichiometry and thermodynamics for learning kinetics from reactor data - Tim Kircher; Felix A. Döppel; Martin Votsmeier (Chemical Engineering Journal, 2024)

Patterns of infringement, risk, and impact driven by coal mining permits in Indonesia - Tim T. Werner; Tessa Toumbourou; Victor Maus; Martin C. Lukas; Laura J. Sonter; Muhamad Muhdar; Rebecca K. Runting; Anthony Bebbington (Ambio, 2024)
Coal mining is known for its contributions to climate change, but its impacts on the environment and human lives near mine sites are less widely recognised. This study integrates remote sensing, GIS, stakeholder interviews and extensive review of provincial data and documents to identify patterns of infringement, risk and impact driven by coal mining expansion across East Kalimantan, Indonesia. Specifically, we map and analyse patterns of mining concessions, land clearing, water cover, human settlement, and safety risks, and link them with mining governance and regulatory infractions related to coal mining permits. We show that excessive, improper permit granting and insufficient monitoring and oversight have led to deforestation, widespread overlaps of concessions with settlements, extensive boundary and regulatory violations, lacking reclamation, and numerous deaths. As the world’s largest thermal coal exporter, Indonesia’s elevated coal infringements, risks, and impacts translate to supply chain, sustainability, and human rights concerns for global coal markets.

Regional phytoliths from the Coastal Cordillera of the Atacama Desert, Chile, and their potential for paleoecological reconstructions - Bárbara D. Vargas-Machuca; Dolores R. Piperno; Tim Böhnert; Alexandra Stoll; Antonio Maldonado; Gina Arancio; Volker Wennrich; Martin Melles (Quaternary International, 2024)

Process model design for positive displacement compressors and their experimental validation: Comparison of Optimal Experimental Design and Machine Learning - Christian Vering; Julian Möntenich; Martin Rätz; Tim Klebig; Rita Streblow; Dirk Müller (International Journal of Refrigeration, 2024)

Verbenone—the universal bark beetle repellent? Its origin, effects, and ecological roles - Tobias Frühbrodt; Martin Schebeck; Martin N. Andersson; Gerrit Holighaus; Jürgen Kreuzwieser; Tim Burzlaff; Horst Delb; Peter H. W. Biedermann (Journal of Pest Science, 2024)
Bark beetles (Curculionidae: Scolytinae) spend most of their life in tissues of host plants, with several species representing economically relevant pests. Their behaviour is largely guided by complex olfactory cues. The compound verbenone was discovered early in the history of bark beetle pheromone research and is now sometimes referred to as a ‘universal bark beetle repellent’. However, some studies aiming to protect trees with verbenone have failed. In fact, most research effort has gone into applied studies, leaving many questions regarding the ecological functions of verbenone for various species unanswered. Here, we review and analyse the scientific literature from more than 50 years. Behavioural responses to verbenone are common among pest bark beetles (< 1% of scolytine species studied so far). Indeed, attraction is inhibited in 38 species from 16 genera, while some secondary species are unaffected or even attracted to verbenone. It is not clear whether the beetles can control the biosynthesis of verbenone; its release may not be an active signal by the beetles, but a passive cue resulting from microorganisms during host colonisation. In this context, we advocate to recognise a bark beetle and its microbiome as an entity (‘holobiont’), to better understand temporal release patterns and deduce the specific function of verbenone for a given species. Surprisingly, natural enemies are not commonly attracted by verbenone, but more taxa need to be studied. A better understanding of the ecological functions of verbenone will help to make verbenone-based tools more effective and improve integrated pest management strategies.

COMPASSO mission and its iodine clock: outline of the clock design - Frederik Kuschewski; Jan Wüst; Markus Oswald; Tim Blomberg; Martin Gohlke; Jonas Bischof; Alex Boac; Tasmim Alam; André Bußmeier; Klaus Abich; Niklas Röder; Klaus Döringshoff; et al. (GPS Solutions, 2024)
One of the limiting factors for GNSS geolocation capabilities is the clock technology deployed on the satellites and the knowledge of the satellite position. Consequently, there are numerous ongoing efforts to improve the stability of space-deployable clocks for next-generation GNSS. The COMPASSO mission is a German Aerospace Center (DLR) project to demonstrate high-performance quantum optical technologies in space with two laser-based absolute frequency references, a frequency comb and a laser communication and ranging terminal establishing a link with the ground station located in Oberpfaffenhofen, Germany. A successful mission will strongly improve the timing stability of space-deployable clocks, demonstrate time transfer between different clocks and allow for ranging in the mm-range. Thus, the technology is a strong candidate for future GNSS satellite clocks and offers possibilities for novel satellite system architectures and can improve the performance of scientific instruments as well. The COMPASSO payload will be delivered to the international space station in 2025 for a mission time of 2 years. In this article, we will highlight the key systems and functionalities of COMPASSO, with the focus set to the absolute frequency references.

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Evaluation of cataract formation in fish exposed to environmental radiation at Chernobyl and Fukushima - Adélaïde Lerebours; Justyn Regini; Roy A. Quinlan; Toshihiro Wada; Barbara Pierscionek; Martin Devonshire; Alexia A. Kalligeraki; Alice Uwineza; Laura Young; John M. Girkin; Phil Warwick; Kurt Smith; et al. (Science of The Total Environment, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

Deep meadows: Deep‐water seagrass habitats revealed - Belinda C. Martin; Ana Giraldo‐Ospina; Sahira Bell; Marion Cambridge; Matthew W. Fraser; Brooke Gibbons; Euan S. Harvey; Gary A. Kendrick; Tim Langlois; Claude Spencer; Renae K. Hovey (Ecology, 2023)

Virtual screening and biological evaluation to identify pharmaceuticals potentially causing hypertension and hypokalemia by inhibiting steroid 11β-hydroxylase - Marie-Christin Jäger; Jacek Kędzierski; Victoria Gell; Tim Wey; Jakub Kollár; Denise V. Winter; Daniela Schuster; Martin Smieško; Alex Odermatt (Toxicology and Applied Pharmacology, 2023)

Comparison of the effects of long-lasting static stretching and hypertrophy training on maximal strength, muscle thickness and flexibility in the plantar flexors - Konstantin Warneke; Klaus Wirth; Michael Keiner; Lars H. Lohmann; Martin Hillebrecht; Anna Brinkmann; Tim Wohlann; Stephan Schiemann (European Journal of Applied Physiology, 2023)
Maximal strength measured via maximal voluntary contraction is known as a key factor in competitive sports performance as well as injury risk reduction and rehabilitation. Maximal strength and hypertrophy are commonly trained by performing resistance training programs. However, literature shows that long-term, long-lasting static stretching interventions can also produce significant improvements in maximal voluntary contraction. The aim of this study is to compare increases in maximal voluntary contraction, muscle thickness and flexibility after 6 weeks of stretch training and conventional hypertrophy training. Sixty-nine (69) active participants ( f = 30, m = 39; age 27.4 ± 4.4 years, height 175.8 ± 2.1 cm, and weight 79.5 ± 5.9 kg) were divided into three groups: IG1 stretched the plantar flexors continuously for one hour per day, IG2 performed hypertrophy training for the plantar flexors (5 × 10–12 reps, three days per week), while CG did not undergo any intervention. Maximal voluntary contraction, muscle thickness, pennation angle and flexibility were the dependent variables. The results of a series of two-way ANOVAs show significant interaction effects ( p < 0.05) for maximal voluntary contraction ( ƞ 2 = 0.143–0.32, p < 0.006), muscle thickness ( ƞ 2 = 0.11–0.14, p < 0.021), pennation angle ( ƞ 2 = 0.002–0.08, p = 0.077–0.625) and flexibility ( ƞ 2 = 0.089–0.21, p < 0.046) for both the stretch and hypertrophy training group without significant differences ( p = 0.37–0.99, d = 0.03–0.4) between both intervention groups. Thus, it can be hypothesized that mechanical tension plays a crucial role in improving maximal voluntary contraction and muscle thickness irrespective whether long-lasting stretching or hypertrophy training is used. Results show that for the calf muscle, the use of long-lasting stretching interventions can be deemed an alternative to conventional resistance training if the aim is to increase maximal voluntary contraction, muscle thickness and flexibility. However, the practical application seems to be strongly limited as a weekly stretching duration of up to 7 h a week is opposed by 3 × 15 min of common resistance training.

Biases in wind speed measurements due to anemometer changes - Cesar Azorin-Molina; Amir Ali Safaei Pirooz; Shalenys Bedoya-Valestt; Eduardo Utrabo-Carazo; Miguel Andres-Martin; Cheng Shen; Lorenzo Minola; Jose A. Guijarro; Enric Aguilar; Manola Brunet; Richard G.J. Flay; Sergio M. Vicente-Serrano; et al. (Atmospheric Research, 2023)

Using fish swimming ability to refine criteria for fishway construction in Myanmar - John Conallin; Nyi Nyi Tun; Aye Myint Swe; Lee J. Baumgartner; Zau Lunn; Martin Mallen-Cooper; Tim Marsden; Nathan Ning; Wayne Robinson; Lalantha Senevirathna; Peter Thew (Fisheries Research, 2023)

What potential does the EU Single-Use Plastics Directive have for reducing plastic pollution at coastlines and riversides? An evaluation based on citizen science data - Tim Kiessling; Mandy Hinzmann; Linda Mederake; Sinja Dittmann; Dennis Brennecke; Marianne Böhm-Beck; Katrin Knickmeier; Martin Thiel (Waste Management, 2023)

Selection of food cultures with protective properties for cooked ham - Valentina Alessandria; Ilario Ferrocino; Valerio Carta; Veronique Zuliani; Tim Martin Seibert; Jakob Soeltoft-Jensen; Kalliopi Rantsiou; Luca Cocolin (Food Microbiology, 2023)

Warmer winters result in reshaping of the European beech forest soil microbiome (bacteria, archaea and fungi)—With potential implications for ecosystem functioning - Mathilde Borg Dahl; Juergen Kreyling; Sebastian Petters; Haitao Wang; Martin Steen Mortensen; Lorrie Maccario; Søren J. Sørensen; Tim Urich; Robert Weigel (Environmental Microbiology, 2023)
In temperate regions, climate warming alters temperature and precipitation regimes. During winter, a decline in insulating snow cover changes the soil environment, where especially frost exposure can have severe implications for soil microorganisms and subsequently for soil nutrient dynamics. Here, we investigated winter climate change responses in European beech forests soil microbiome. Nine study sites with each three treatments (snow exclusion, insolation, and ambient) were investigated. Long‐term adaptation to average climate was explored by comparing across sites. Triplicated treatment plots were used to evaluate short‐term (one single winter) responses. Community profiles of bacteria, archaea and fungi were created using amplicon sequencing. Correlations between the microbiome, vegetation and soil physicochemical properties were found. We identify core members of the forest‐microbiome and link them to key processes, for example, mycorrhizal symbiont and specialized beech wood degraders (fungi) and nitrogen cycling (bacteria, archaea). For bacteria, the shift of the microbiome composition due to short‐term soil temperature manipulations in winter was similar to the community differences observed between long‐term relatively cold to warm conditions. The results suggest a strong link between the changes in the microbiomes and changes in environmental processes, for example, nitrogen dynamics, driven by variations in winter climate.

Mineral effects on chemical and physical transformations of fast pyrolysis products of cellulose-based model fuels in N2 and CO2 - Till Eckhard; Christin Pflieger; Carmela Russo; Erik Freisewinkel; Tim Eisenbach; Jannik Böttger; Osvalda Senneca; Barbara Apicella; Martin Schiemann; Roland Span; Viktor Scherer; Martin Muhler; et al. (Fuel, 2023)

An observing campaign to search for meteoroids of Bennu at Earth - Peter Jenniskens; Dante S. Lauretta; Lindsey R. Koelbel; Martin C. Towner; Phil Bland; Steve Heathcote; Timothy M.C. Abbott; Emmanuel Jehin; Toni Hanke; Elise Fahl; Rynault van Wyk; Tim Cooper; et al. (Icarus, 2023)

Demographic consequences of changes in environmental periodicity - Eva Conquet; Arpat Ozgul; Daniel T. Blumstein; Kenneth B. Armitage; Madan K. Oli; Julien G. A. Martin; Tim H. Clutton‐Brock; Maria Paniw (Ecology, 2023)
The fate of natural populations is mediated by complex interactions among vital rates, which can vary within and among years. Although the effects of random, among‐year variation in vital rates have been studied extensively, relatively little is known about how periodic, nonrandom variation in vital rates affects populations. This knowledge gap is potentially alarming as global environmental change is projected to alter common periodic variations, such as seasonality. We investigated the effects of changes in vital‐rate periodicity on populations of three species representing different forms of adaptation to periodic environments: the yellow‐bellied marmot ( Marmota flaviventer ), adapted to strong seasonality in snowfall; the meerkat ( Suricata suricatta ), adapted to inter‐annual stochasticity as well as seasonal patterns in rainfall; and the dewy pine ( Drosophyllum lusitanicum ), adapted to fire regimes and periodic post‐fire habitat succession. To assess how changes in periodicity affect population growth, we parameterized periodic matrix population models and projected population dynamics under different scenarios of perturbations in the strength of vital‐rate periodicity. We assessed the effects of such perturbations on various metrics describing population dynamics, including the stochastic growth rate, log λ S . Overall, perturbing the strength of periodicity had strong effects on population dynamics in all three study species. For the marmots, log λ S decreased with increased seasonal differences in adult survival. For the meerkats, density dependence buffered the effects of perturbations of periodicity on log λ S . Finally, dewy pines were negatively affected by changes in natural post‐fire succession under stochastic or periodic fire regimes with fires occurring every 30 years, but were buffered by density dependence from such changes under presumed more frequent fires or large‐scale disturbances. We show that changes in the strength of vital‐rate periodicity can have diverse but strong effects on population dynamics across different life histories. Populations buffered from inter‐annual vital‐rate variation can be affected substantially by changes in environmentally driven vital‐rate periodic patterns; however, the effects of such changes can be masked in analyses focusing on inter‐annual variation. As most ecosystems are affected by periodic variations in the environment such as seasonality, assessing their contributions to population viability for future global‐change research is crucial.

Modelling potential natural pest control ecosystem services provided by arthropods in agricultural landscapes - Marie Perennes; Tim Diekötter; Hannes Hoffmann; Emily A. Martin; Boris Schröder; Benjamin Burkhard (Agriculture, Ecosystems & Environment, 2023)

Generation & characterization of expandable human liver sinusoidal endothelial cells and their application to assess hepatotoxicity in an advanced in vitro liver model - Tim Kaden; Astrid Noerenberg; Jennifer Boldt; Carolin Sagawe; Timo Johannssen; Knut Rennert; Martin Raasch; Torge Evenburg (Toxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Potassium permanganate is an excellent alternative to osmium tetroxide in freeze-substitution - Martin Schauflinger; Tim Bergner; Gregor Neusser; Christine Kranz; Clarissa Read (Histochemistry and Cell Biology, 2022)
High-pressure freezing followed by freeze-substitution is a valuable method for ultrastructural analyses of resin-embedded biological samples. The visualization of lipid membranes is one of the most critical aspects of any ultrastructural study and can be especially challenging in high-pressure frozen specimens. Historically, osmium tetroxide has been the preferred fixative and staining agent for lipid-containing structures in freeze-substitution solutions. However, osmium tetroxide is not only a rare and expensive material, but also volatile and toxic. Here, we introduce the use of a combination of potassium permanganate, uranyl acetate, and water in acetone as complementing reagents during the freeze-substitution process. This mix imparts an intense en bloc stain to cellular ultrastructure and membranes, which makes poststaining superfluous and is well suited for block-face imaging. Thus, potassium permanganate can effectively replace osmium tetroxide in the freeze-substitution solution without sacrificing the quality of ultrastructural preservation.

The Oceans 2.0/3.0 Data Management and Archival System - Dwight Owens; Dilumie Abeysirigunawardena; Ben Biffard; Yan Chen; Patrick Conley; Reyna Jenkyns; Shane Kerschtien; Tim Lavallee; Melissa MacArthur; Jina Mousseau; Kim Old; Meghan Paulson; et al. (Frontiers in Marine Science, 2022)
The advent of large-scale cabled ocean observatories brought about the need to handle large amounts of ocean-based data, continuously recorded at a high sampling rate over many years and made accessible in near-real time to the ocean science community and the public. Ocean Networks Canada (ONC) commenced installing and operating two regional cabled observatories on Canada’s Pacific Coast, VENUS inshore and NEPTUNE offshore in the 2000s, and later expanded to include observatories in the Atlantic and Arctic in the 2010s. The first data streams from the cabled instrument nodes started flowing in February 2006. This paper describes Oceans 2.0 and Oceans 3.0 , the comprehensive Data Management and Archival System that ONC developed to capture all data and associated metadata into an ever-expanding dynamic database. Oceans 2.0 was the name for this software system from 2006–2021; in 2022, ONC revised this name to Oceans 3.0, reflecting the system’s many new and planned capabilities aligning with Web 3.0 concepts. Oceans 3.0 comprises both tools to manage the data acquisition and archival of all instrumental assets managed by ONC as well as end-user tools to discover, process, visualize and download the data. Oceans 3.0 rests upon ten foundational pillars: (1) A robust and stable system architecture to serve as the backbone within a context of constant technological progress and evolving needs of the operators and end users; (2) a data acquisition and archival framework for infrastructure management and data recording, including instrument drivers and parsers to capture all data and observatory actions, alongside task management options and support for data versioning; (3) a metadata system tracking all the details necessary to archive Findable, Accessible, Interoperable and Reproducible (FAIR) data from all scientific and non-scientific sensors; (4) a data Quality Assurance and Quality Control lifecycle with a consistent workflow and automated testing to detect instrument, data and network issues; (5) a data product pipeline ensuring the data are served in a wide variety of standard formats; (6) data discovery and access tools, both generalized and use-specific, allowing users to find and access data of interest; (7) an Application Programming Interface that enables scripted data discovery and access; (8) capabilities for customized and interactive data handling such as annotating videos or ingesting individual campaign-based data sets; (9) a system for generating persistent data identifiers and data citations, which supports interoperability with external data repositories; (10) capabilities to automatically detect and react to emergent events such as earthquakes. With a growing database and advancing technological capabilities, Oceans 3.0 is evolving toward a future in which the old paradigm of downloading packaged data files transitions to the new paradigm of cloud-based environments for data discovery, processing, analysis, and exchange.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hydraulic traits of co-existing conifers do not correlate with local hydroclimate condition: a case study in the northern Rocky Mountains, U.S.A - Tim Clute; Justin Martin; Nate Looker; Jia Hu (Oecologia, 2021)

Electric signal synchronization as a behavioural strategy to generate social attention in small groups of mormyrid weakly electric fish and a mobile fish robot - Martin Worm; Tim Landgraf; Gerhard von der Emde (Biological Cybernetics, 2021)
African weakly electric fish communicate at night by constantly emitting and perceiving brief electrical signals (electric organ discharges, EOD) at variable inter-discharge intervals (IDI). While the waveform of single EODs contains information about the sender’s identity, the variable IDI patterns convey information about its current motivational and behavioural state. Pairs of fish can synchronize their EODs to each other via echo responses, and we have previously formulated a ‘social attention hypothesis’ stating that fish use echo responses to address specific individuals and establish brief dyadic communication frameworks within a group. Here, we employed a mobile fish robot to investigate the behaviour of small groups of up to four Mormyrus rume and characterized the social situations during which synchronizations occurred. An EOD-emitting robot reliably evoked social following behaviour, which was strongest in smaller groups and declined with increasing group size. We did not find significant differences in motor behaviour of M. rume with either an interactive playback (echo response) or a random control playback by the robot. Still, the robot reliably elicited mutual synchronizations with other fish. Synchronizations mostly occurred during relatively close social interactions, usually when the fish that initiated synchronization approached either the robot or another fish from a distance. The results support our social attention hypothesis and suggest that electric signal synchronization might facilitate the exchange of social information during a wide range of social behaviours from aggressive territorial displays to shoaling and even cooperative hunting in some mormyrids.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Current Trends and Future Directions of Large Scale Image and Video Annotation: Observations From Four Years of BIIGLE 2.0 - Martin Zurowietz; Tim W. Nattkemper (Frontiers in Marine Science, 2021)
Marine imaging has evolved from small, narrowly focussed applications to large-scale applications covering areas of several hundred square kilometers or time series covering observation periods of several months. The analysis and interpretation of the accumulating large volume of digital images or videos will continue to challenge the marine science community to keep this process efficient and effective. It is safe to say that any strategy will rely on some software platform supporting manual image and video annotation, either for a direct manual annotation-based analysis or for collecting training data to deploy a machine learning–based approach for (semi-)automatic annotation. This paper describes how computer-assisted manual full-frame image and video annotation is currently performed in marine science and how it can evolve to keep up with the increasing demand for image and video annotation and the growing volume of imaging data. As an example, observations are presented how the image and video annotation tool BIIGLE 2.0 has been used by an international community of more than one thousand users in the last 4 years. In addition, new features and tools are presented to show how BIIGLE 2.0 has evolved over the same time period: video annotation, support for large images in the gigapixel range, machine learning assisted image annotation, improved mobility and affordability, application instance federation and enhanced label tree collaboration. The observations indicate that, despite novel concepts and tools introduced by BIIGLE 2.0, full-frame image and video annotation is still mostly done in the same way as two decades ago, where single users annotated subsets of image collections or single video frames with limited computational support. We encourage researchers to review their protocols for education and annotation, making use of newer technologies and tools to improve the efficiency and effectivity of image and video annotation in marine science.

Oxygen and Nutrient Trapping in the Southern Benguela Upwelling System - Tim Rixen; Niko Lahajnar; Tarron Lamont; Rolf Koppelmann; Bettina Martin; Justus E. E. van Beusekom; Claire Siddiqui; Keshnee Pillay; Luisa Meiritz (Frontiers in Marine Science, 2021)
The Benguela Upwelling System in the southeast Atlantic Ocean is of crucial socio-economic importance due to its high productivity. However, predicting its response to global change and understanding past changes are still great challenges. Here, we compile data obtained from a research cruise and an oceanographic mooring to demonstrate that a topographically steered nutrient trapping zone develops in a narrow belt along the coast during the main upwelling season in austral spring and summer in the southern Benguela Upwelling System. High nutrient concentrations within this zone increase the impact of upwelling on the productivity of the southern Benguela Upwelling System, but the efficient nutrient trapping operates at the expense of decreasing oxygen concentrations. This enhances the probability of anoxic events emerging toward the end of the upwelling season. However, at the end of the upwelling season, the front that separates the coastally trapped waters from open shelf waters weakens or even collapses due to upwelling cessation and the reversing current regime. This, in addition to a stronger vertical mixing caused by winter cooling, fosters the ventilation of the nutrient trapping zone, which reestablishes during the following upwelling season. The postulated intensification of upwelling and changes in the ecosystem structure in response to global warming seem to reduce the nutrient trapping efficiency by increasing offshore advection of surface waters and plankton blooms. The intensified upwelling and resulting lower biological oxygen consumption appears to mask the expected impacts of global warming on the oxygen minimum zone (OMZ) in the southern Benguela Upwelling System. In contrast to other OMZs, including those in northern Benguela Upwelling Systems, the OMZ in the southern Benguela Upwelling System reveals so far no detectable long-term decrease in oxygen. Thus, the nutrient trapping efficiency seems to be a critical feature mitigating global change impacts on the southern Benguela Upwelling System. Since it is topographically steered, regional impacts on the nutrient trapping efficiency appear also to explain varying responses of upwelling systems to global change as the comparison between southern and northern Benguela Upwelling System shows. This emphasizes the need for further and more comparable studies in order to better understand the response of Eastern Boundary Upwelling Systems and their ecosystem services to global change.

Optical clock technologies for global navigation satellite systems - Thilo Schuldt; Martin Gohlke; Markus Oswald; Jan Wüst; Tim Blomberg; Klaus Döringshoff; Ahmad Bawamia; Andreas Wicht; Matthias Lezius; Kai Voss; Markus Krutzik; Sven Herrmann; et al. (GPS Solutions, 2021)
Future generations of global navigation satellite systems (GNSSs) can benefit from optical technologies. Especially optical clocks could back-up or replace the currently used microwave clocks, having the potential to improve GNSS position determination enabled by their lower frequency instabilities. Furthermore, optical clock technologies—in combination with optical inter-satellite links—enable new GNSS architectures, e.g., by synchronization of distant optical frequency references within the constellation using time and frequency transfer techniques. Optical frequency references based on Doppler-free spectroscopy of molecular iodine are seen as a promising candidate for a future GNSS optical clock. Compact and ruggedized setups have been developed, showing frequency instabilities at the 10 –15 level for averaging times between 1 s and 10,000 s. We introduce optical clock technologies for applications in future GNSS and present the current status of our developments of iodine-based optical frequency references.

Competition and pollen wars: simulations reveal the dynamics of competition mediated through heterospecific pollen transfer by non-flower constant insects - Alan Dorin; Tim Taylor; Martin Burd; Julian Garcia; Mani Shrestha; Adrian G. Dyer (Theoretical Ecology, 2021)

Correction to: Hydraulic traits of co-existing conifers do not correlate with local hydroclimate condition: a case study in the northern Rocky Mountains, U.S.A - Tim Clute; Justin Martin; Nate Looker; Jia Hu (Oecologia, 2021)

Tag use to monitor fish behaviour in aquaculture: a review of benefits, problems and solutions - Georgia Macaulay; Fletcher Warren‐Myers; Luke T. Barrett; Frode Oppedal; Martin Føre; Tim Dempster (Reviews in Aquaculture, 2021)
A variety of tagging techniques are now available to monitor fish behaviour, physiology and their environmental experience. Tagging is frequently used in aquaculture research to monitor free‐swimming individuals within farmed populations. However, for information gathered from tagged fish to be representative of farmed populations, tagging must not fundamentally affect fish behaviour, physiology or survival. Here, we systematically review studies that used tags to monitor farmed fish behaviour and test factors that affect tag retrieval and tag‐related mortality. Most studies using tags assessed movement and swimming behaviour in salmonids, predominantly in Europe and North America. Mortality of tagged fish was 10 times higher in sea‐cages (mean = 25%, range = 0–61.5%, n = 22 studies) than in tanks (mean = 2.5%, range = 0–17%, n = 23 studies), while mortality of tagged fish in sea‐cages was markedly higher in longer trials (from 4% in single day trials to 36% after 100 days). Higher‐than‐usual mortality rates among tagged fish, together with largely unknown sublethal effects on behaviour, should caution against using tagging studies to make decisions related to farm management. Moreover, key metrics such as mortality rates of tagged and untagged fish or evidence of sublethal effects are often unreported. We make several recommendations to improve future tagging studies and increase transparency in reporting. A greater insight into the causes of tagged fish mortality in sea‐cages is required to secure animal welfare and data validity in studies that use tags to assess fish behaviour in aquaculture.

Characterizing Canopy Openness in Open Forests: Spherical Densiometer and Canopy Photography Are Equivalent but Less Sensitive than Direct Measurements of Solar Radiation - Emily Russavage; Jake Thiele; Joanna Lumbsden-Pinto; Kathy Schwager; Tim Green; Martin Dovciak (Journal of Forestry, 2021)
In forest ecosystems, canopy openness affects understory light availability, plant growth, and tree species recruitment, thus shaping future forest composition, structure, and functional diversity. Foresters must correctly and quickly measure canopy openness to meet their management objectives. To help guide the selection of an appropriate method for measuring canopy openness, we compared three common techniques that vary in cost, complexity, and time required for measurements and data processing: smartphone-based hemispherical photography, spherical densiometer measurements, and direct measurements of solar radiation (using AccuPAR ceptometer). We measured canopy openness using these three methods on 28 permanent forest health monitoring plots in pine-oak forests of the Central Pine Barrens of Long Island in New York State. By analysis of variance and regression analyses, we found the three methods (particularly densiometer and hemispherical photographs) yielded broadly equivalent and strongly positively correlated descriptions of canopy openness. The direct measurements of solar radiation seemed to have a greater potential to detect subtle variation in forest understory light. Forest managers may sufficiently characterize canopy openness using quick and cheap methods (e.g., spherical densiometers) and avoid larger costs of devices for direct light measurements (e.g., ceptometers) and the larger data-processing times of hemispherical photography.

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Numerical investigation on rigid and flexible pipelines embedded in granular and self-compacting materials - Khalid Abdel-Rahman; Tim Gerlach; Martin Achmus (Innovative Infrastructure Solutions, 2020)
Self-compacting filling material or controlled low-strength material (CLSM) is a cementitious material which is liquid during filling, and it is used primarily as backfill, e.g., in trenches. Several products are currently used as CLSM such as flowable fill, controlled density fill, flowable mortar and low-strength plastic soil–cement. The low-strength requirement is necessary to allow for future excavation of CLSM. A two-dimensional numerical model was developed using the finite element system ABAQUS. In this model, the material behavior of granular soil and CLSM is described using an elasto-plastic constitutive model with Mohr–Coulomb failure criterion. Rigid and flexible pipes were modeled once embedded in sandy soil and once embedded in self-compacting material. The numerical model allows the modeling of the effect of hardening process on the overall behavior of the pipe–soil system. The main objective of this study is to investigate the behavior of rigid and flexible pipelines embedded in CLSM as a filling material numerically and to show advantages and disadvantages in comparison with the presently widely used filling materials like sand.

Predators, Disease, and Environmental Change in the Nearshore Ecosystem: Mortality in Southern Sea Otters (Enhydra lutris nereis) From 1998–2012 - Melissa A. Miller; Megan E. Moriarty; Laird Henkel; Martin Tim Tinker; Tristan L. Burgess; Francesca I. Batac; Erin Dodd; Colleen Young; Michael D. Harris; David A. Jessup; Jack Ames; Patricia A. Conrad; et al. (Frontiers in Marine Science, 2020)
We compiled findings from 15 years (1998–2012) of southern sea otter ( Enhydra lutris nereis ) necropsies, incorporating data from 560 animals. Sensitive diagnostic tests were used to detect biotoxins, bacteria, parasites and fungi. Methods to classify primary and contributing causes of death (COD) and sequelae utilized an updated understanding of health risks affecting this population. Several interesting patterns emerged, including identification of coastal regions of high mortality risk for sea otter mortality due to shark bite, cardiomyopathy, toxoplasmosis, sarcocystosis, acanthocephalan peritonitis and coccidioidomycosis. We identified demographic attributes that enhanced the risk of disease in relation to age, sex, and reproductive stage. Death due to white shark ( Carcharodon carcharias ) bite increased dramatically during the study period and was the most common primary COD. However, when primary and contributing COD were combined, the most prevalent COD was infectious disease (affecting 63% of otters), especially fatal infections by acanthocephalans ( Profilicollis spp.) and protozoa (e.g., Sarcocystis neurona and Toxoplasma gondii ). Fatal bacterial infections were also extremely common as a primary process or a sequela, affecting 68% of examined otters. Substantial advances were made in identifying sea otters that died following exposure to the pervasive marine neurotoxin domoic acid (DA), and DA intoxication was conservatively estimated as a primary or contributing COD for 20% of otters. Cardiomyopathy was also highly prevalent as a primary or contributing COD (41%) and exhibited significant associations with DA intoxication and protozoal infection. For adult and aged adult females in late pup care through post-weaning at the time of death, 83% had end lactation syndrome (ELS) as a primary or contributing COD. This comprehensive longitudinal dataset is unique in its depth and scope. The large sample size and extensive time period provided an opportunity to investigate mortality patterns in a changing environment and identify spatial and temporal disease “hot spots” and emerging threats. Our findings will help improve estimates of population-level impacts of specific threats and optimize conservation and environmental mitigation efforts for this threatened species.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Corrigendum: BIIGLE 2.0 - Browsing and Annotating Large Marine Image Collections - Daniel Langenkämper; Martin Zurowietz; Timm Schoening; Tim W. Nattkemper (Frontiers in Marine Science, 2020)

Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Rosie Chance; Liselotte Tinel; Amit Sarkar; Alok K. Sinha; Anoop S. Mahajan; Racheal Chacko; P. Sabu; Rajdeep Roy; Tim D. Jickells; David P. Stevens; Martin Wadley; Lucy J. Carpenter (Frontiers in Marine Science, 2020)

Compromised Hippocampal Neuroplasticity in the Interferon-α and Toll-like Receptor-3 Activation-Induced Mouse Depression Model - Eduardo H. Sanchez-Mendoza; Santiago Camblor-Perujo; Luiza Martins Nascentes-Melo; Egor Dzyubenko; Michael Fleischer; Tayana Silva de Carvalho; Linda-Isabell Schmitt; Markus Leo; Tim Hagenacker; Arne Herring; Kathy Keyvani; Sujoy Bera; et al. (Molecular Neurobiology, 2020)
Disrupted neuronal plasticity due to subtle inflammation is considered to play a fundamental role in the pathogenesis of major depressive disorder. Interferon-α (IFN-α) potentiates immune responses against viral pathogens that induce toll-like receptor-3 (TLR3) activation but evokes severe major depressive disorder in humans by mechanisms that remain insufficiently described. By using a previously established mouse model of depression induced by combined delivery of IFN-α and polyinosinic:polycytidylic acid (poly(I:C)), a TLR3 agonist, we provide evidence that IFN-α and poly(I:C) reduce apical dendritic spine density in the hippocampal CA1 area ex vivo via mechanisms involving decreased TrkB signaling. In vitro, IFN-α and poly(I:C) treatments required neuronal activity to reduce dendritic spine density and TrkB signaling. The levels of presynaptic protein vesicular glutamate transporter (VGLUT)-1 and postsynaptic protein postsynaptic density-95 (PSD95) were specifically decreased, whereas the expression of both synaptic and extrasynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor 1 (AMPAR1) was increased by IFN-α and poly(I:C) delivery. Patch clamp recordings in primary hippocampal neurons revealed that morphological changes at the synapse induced by IFN-α and poly(I:C) costimulation were accompanied by an increased action potential threshold and action potential frequency, indicative of impaired neuronal excitability. Taken together, IFN-α and poly(I:C) delivery leads to structural and functional alterations at the synapse indicating that compromised neuroplasticity may play an integral role in the pathogenesis of immune response-induced depression.

A probabilistic seismic hazard assessment for Wylfa Newydd, a new nuclear site in the United Kingdom - Manuela Villani; Zygmunt Lubkowski; Matthew Free; Roger M. W. Musson; Barbara Polidoro; Rory McCully; Areti Koskosidi; Crispin Oakman; Tim Courtney; Martin Walsh (Bulletin of Earthquake Engineering, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Intertwined effects of climate and land use change on environmental dynamics and carbon accumulation in a mangrove‐fringed coastal lagoon in Java, Indonesia - K. Anggi Hapsari; Tim C. Jennerjahn; Martin C. Lukas; Volker Karius; Hermann Behling (Global Change Biology, 2020)
The identification and quantification of natural carbon (C) sinks is critical to global climate change mitigation efforts. Tropical coastal wetlands are considered important in this context, yet knowledge of their dynamics and quantitative data are still scarce. In order to quantify the C accumulation rate and understand how it is influenced by land use and climate change, a palaeoecological study was conducted in the mangrove‐fringed Segara Anakan Lagoon (SAL) in Java, Indonesia. A sediment core was age‐dated and analyzed for its pollen and spore, elemental and biogeochemical compositions. The results indicate that environmental dynamics in the SAL and its C accumulation over the past 400 years were controlled mainly by climate oscillations and anthropogenic activities. The interaction of these two factors changed the lagoon's sediment supply and salinity, which consequently altered the organic matter composition and deposition in the lagoon. Four phases with varying climates were identified. While autochthonous mangrove C was a significant contributor to carbon accumulation in SAL sediments throughout all four phases, varying admixtures of terrestrial C from the hinterland also contributed, with natural mixed forest C predominating in the early phases and agriculture soil C predominating in the later phases. In this context, climate‐related precipitation changes are an overarching control, as surface water transport through rivers serves as the “delivery agent” for the outcomes of the anthropogenic impact in the catchment area into the lagoon. Amongst mangrove‐dominated ecosystems globally, the SAL is one of the most effective C sinks due to high mangrove carbon input in combination with a high allochthonous carbon input from anthropogenically enhanced sediment from the hinterland and increased preservation. Given the substantial C sequestration capacity of the SAL and other mangrove‐fringed coastal lagoons, conservation and restoration of these ecosystems is vitally important for climate change mitigation.

Interacting adipose-derived stem cells and microvascular endothelial cells provide a beneficial milieu for soft tissue healing - Sophie Bachmann; Martina Jennewein; Monika Bubel; Silke Guthörl; Tim Pohlemann; Martin Oberringer (Molecular Biology Reports, 2020)

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

More Than 50 Years of Successful Continuous Temperature Section Measurements by the Global Expendable Bathythermograph Network, Its Integrability, Societal Benefits, and Future - Gustavo J. Goni; Janet Sprintall; Francis Bringas; Lijing Cheng; Mauro Cirano; Shenfu Dong; Ricardo Domingues; Marlos Goes; Hosmay Lopez; Rosemary Morrow; Ulises Rivero; Thomas Rossby; et al. (Frontiers in Marine Science, 2019)

Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean - Alexander V. Babanin; W. Erick Rogers; Ricardo de Camargo; Martin Doble; Tom Durrant; Kirill Filchuk; Kevin Ewans; Mark Hemer; Tim Janssen; Boris Kelly-Gerreyn; Keith Machutchon; Peter McComb; et al. (Frontiers in Marine Science, 2019)

Species Matter: Wood Density Influences Tropical Forest Biomass at Multiple Scales - Oliver L. Phillips; Martin J. P. Sullivan; Tim R. Baker; Abel Monteagudo Mendoza; Percy Núñez Vargas; Rodolfo Vásquez (Surveys in Geophysics, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Sozialer Status und Spendenverhalten Ehrenamtlicher in Sportvereinen - Eike Emrich; Martin Hämmerle; Christoph Behrens; Tim Meyer; Christian Pierdzioch (German Journal of Exercise and Sport Research, 2018)

Running off the road: roadside non-native plants invading mountain vegetation - Keith L. McDougall; Jonas Lembrechts; Lisa J. Rew; Sylvia Haider; Lohengrin A. Cavieres; Christoph Kueffer; Ann Milbau; Bridgett J. Naylor; Martin A. Nuñez; Anibal Pauchard; Tim Seipel; Karina L. Speziale; et al. (Biological Invasions, 2018)

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

The role of adipose-derived stem cells in a self-organizing 3D model with regard to human soft tissue healing - Martin Oberringer; Monika Bubel; Martina Jennewein; Silke Guthörl; Tamara Morsch; Sophie Bachmann; Wolfgang Metzger; Tim Pohlemann (Molecular and Cellular Biochemistry, 2018)

A neural network model for familiarity and context learning during honeybee foraging flights - Jurek Müller; Martin Nawrot; Randolf Menzel; Tim Landgraf (Biological Cybernetics, 2018)

Colour polymorphism in the coconut crab (Birgus latro) - Ossi Nokelainen; Martin Stevens; Tim Caro (Evolutionary Ecology, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice - Roy C. Levitt; Gerald Y. Zhuang; Yuan Kang; Diana M. Erasso; Udita Upadhyay; Mehtap Ozdemir; Eugene S. Fu; Konstantinos D. Sarantopoulos; Shad B. Smith; William Maixner; Luda Diatchenko; Eden R. Martin; et al. (Mammalian Genome, 2017)

Soil carbon sequestration due to post‐Soviet cropland abandonment: estimates from a large‐scale soil organic carbon field inventory - Tim‐Martin Wertebach; Norbert Hölzel; Immo Kämpf; Andrey Yurtaev; Sergey Tupitsin; Kathrin Kiehl; Johannes Kamp; Till Kleinebecker (Global Change Biology, 2017)
The break‐up of the Soviet Union in 1991 triggered cropland abandonment on a continental scale, which in turn led to carbon accumulation on abandoned land across Eurasia. Previous studies have estimated carbon accumulation rates across Russia based on large‐scale modelling. Studies that assess carbon sequestration on abandoned land based on robust field sampling are rare. We investigated soil organic carbon ( SOC ) stocks using a randomized sampling design along a climatic gradient from forest steppe to Sub‐Taiga in Western Siberia (Tyumen Province). In total, SOC contents were sampled on 470 plots across different soil and land‐use types. The effect of land use on changes in SOC stock was evaluated, and carbon sequestration rates were calculated for different age stages of abandoned cropland. While land‐use type had an effect on carbon accumulation in the topsoil (0–5 cm), no independent land‐use effects were found for deeper SOC stocks. Topsoil carbon stocks of grasslands and forests were significantly higher than those of soils managed for crops and under abandoned cropland. SOC increased significantly with time since abandonment. The average carbon sequestration rate for soils of abandoned cropland was 0.66 Mg C ha −1 yr −1 (1–20 years old, 0–5 cm soil depth), which is at the lower end of published estimates for Russia and Siberia. There was a tendency towards SOC saturation on abandoned land as sequestration rates were much higher for recently abandoned (1–10 years old, 1.04 Mg C ha −1 yr −1 ) compared to earlier abandoned crop fields (11–20 years old, 0.26 Mg C ha −1 yr −1 ). Our study confirms the global significance of abandoned cropland in Russia for carbon sequestration. Our findings also suggest that robust regional surveys based on a large number of samples advance model‐based continent‐wide SOC prediction.

Steric sea level variability (1993–2010) in an ensemble of ocean reanalyses and objective analyses - Andrea Storto; Simona Masina; Magdalena Balmaseda; Stéphanie Guinehut; Yan Xue; Tanguy Szekely; Ichiro Fukumori; Gael Forget; You-Soon Chang; Simon A. Good; Armin Köhl; Guillaume Vernieres; et al. (Climate Dynamics, 2017)

Evaluation of climate‐related carbon turnover processes in global vegetation models for boreal and temperate forests - Martin Thurner; Christian Beer; Philippe Ciais; Andrew D. Friend; Akihiko Ito; Axel Kleidon; Mark R. Lomas; Shaun Quegan; Tim T. Rademacher; Sibyll Schaphoff; Markus Tum; Andy Wiltshire; et al. (Global Change Biology, 2017)
Turnover concepts in state‐of‐the‐art global vegetation models ( GVM s) account for various processes, but are often highly simplified and may not include an adequate representation of the dominant processes that shape vegetation carbon turnover rates in real forest ecosystems at a large spatial scale. Here, we evaluate vegetation carbon turnover processes in GVM s participating in the Inter‐Sectoral Impact Model Intercomparison Project ( ISI ‐ MIP , including HYBRID 4, JeDi, JULES , LPJ ml, ORCHIDEE , SDGVM , and VISIT ) using estimates of vegetation carbon turnover rate ( k ) derived from a combination of remote sensing based products of biomass and net primary production ( NPP ). We find that current model limitations lead to considerable biases in the simulated biomass and in k (severe underestimations by all models except JeDi and VISIT compared to observation‐based average k ), likely contributing to underestimation of positive feedbacks of the northern forest carbon balance to climate change caused by changes in forest mortality. A need for improved turnover concepts related to frost damage, drought, and insect outbreaks to better reproduce observation‐based spatial patterns in k is identified. As direct frost damage effects on mortality are usually not accounted for in these GVM s, simulated relationships between k and winter length in boreal forests are not consistent between different regions and strongly biased compared to the observation‐based relationships. Some models show a response of k to drought in temperate forests as a result of impacts of water availability on NPP , growth efficiency or carbon balance dependent mortality as well as soil or litter moisture effects on leaf turnover or fire. However, further direct drought effects such as carbon starvation (only in HYBRID 4) or hydraulic failure are usually not taken into account by the investigated GVM s. While they are considered dominant large‐scale mortality agents, mortality mechanisms related to insects and pathogens are not explicitly treated in these models.

Acute liver effects, disposition and metabolic fate of [14C]-fenclozic acid following oral administration to normal and bile-cannulated male C57BL/6J mice - Kathryn Pickup; Scott Martin; Elizabeth A. Partridge; Huw B. Jones; Jonathan Wills; Tim Schulz-Utermoehl; Alan McCarthy; Alison Rodrigues; Chris Page; Kerry Ratcliffe; Sunil Sarda; Ian D. Wilson (Archives of Toxicology, 2017)

Assessing the ecological risk posed by a recently established invasive alien predator: Harmonia axyridis as a case study - Marc Kenis; Tim Adriaens; Peter M. J. Brown; Angelos Katsanis; Gilles San Martin; Etienne Branquart; Dirk Maes; René Eschen; Renate Zindel; Johan Van Vlaenderen; Dirk Babendreier; Helen E. Roy; et al. (BioControl, 2017)

Shelf–Basin interaction along the East Siberian Sea - Leif G. Anderson; Göran Björk; Ola Holby; Sara Jutterström; Carl Magnus Mörth; Matt O'Regan; Christof Pearce; Igor Semiletov; Christian Stranne; Tim Stöven; Toste Tanhua; Adam Ulfsbo; et al. (Ocean Science, 2017)
Extensive biogeochemical transformation of organic matter takes place in the shallow continental shelf seas of Siberia. This, in combination with brine production from sea-ice formation, results in cold bottom waters with relatively high salinity and nutrient concentrations, as well as low oxygen and pH levels. Data from the SWERUS-C3 expedition with icebreaker Oden, from July to September 2014, show the distribution of such nutrient-rich, cold bottom waters along the continental margin from about 140 to 180° E. The water with maximum nutrient concentration, classically named the upper halocline, is absent over the Lomonosov Ridge at 140° E, while it appears in the Makarov Basin at 150° E and intensifies further eastwards. At the intercept between the Mendeleev Ridge and the East Siberian continental shelf slope, the nutrient maximum is still intense, but distributed across a larger depth interval. The nutrient-rich water is found here at salinities of up to ∼ 34.5, i.e. in the water classically named lower halocline. East of 170° E transient tracers show significantly less ventilated waters below about 150 m water depth. This likely results from a local isolation of waters over the Chukchi Abyssal Plain as the boundary current from the west is steered away from this area by the bathymetry of the Mendeleev Ridge. The water with salinities of ∼ 34.5 has high nutrients and low oxygen concentrations as well as low pH, typically indicating decay of organic matter. A deficit in nitrate relative to phosphate suggests that this process partly occurs under hypoxia. We conclude that the high nutrient water with salinity ∼ 34.5 are formed on the shelf slope in the Mendeleev Ridge region from interior basin water that is trapped for enough time to attain its signature through interaction with the sediment.

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

BIIGLE 2.0 - Browsing and Annotating Large Marine Image Collections - Daniel Langenkämper; Martin Zurowietz; Timm Schoening; Tim W. Nattkemper (Frontiers in Marine Science, 2017)

Fluid Dynamics in Rotary Piston Blood Pumps - Johannes Wappenschmidt; Simon J. Sonntag; Martin Buesen; Sascha Gross-Hardt; Tim Kaufmann; Thomas Schmitz-Rode; Ruediger Autschbach; Andreas Goetzenich (Annals of Biomedical Engineering, 2017)

Epigallocatechin gallate (EGCG) inhibits adhesion and migration of neural progenitor cells in vitro - Marta Barenys; Kathrin Gassmann; Christine Baksmeier; Sabrina Heinz; Ingrid Reverte; Martin Schmuck; Thomas Temme; Farina Bendt; Tim-Christian Zschauer; Thomas Dino Rockel; Klaus Unfried; Wim Wätjen; et al. (Archives of Toxicology, 2017)

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

High emissions of greenhouse gases from grasslands on peat and other organic soils - Bärbel Tiemeyer; Elisa Albiac Borraz; Jürgen Augustin; Michel Bechtold; Sascha Beetz; Colja Beyer; Matthias Drösler; Martin Ebli; Tim Eickenscheidt; Sabine Fiedler; Christoph Förster; Annette Freibauer; et al. (Global Change Biology, 2016)
Drainage has turned peatlands from a carbon sink into one of the world's largest greenhouse gas ( GHG ) sources from cultivated soils. We analyzed a unique data set (12 peatlands, 48 sites and 122 annual budgets) of mainly unpublished GHG emissions from grasslands on bog and fen peat as well as other soils rich in soil organic carbon ( SOC ) in Germany. Emissions and environmental variables were measured with identical methods. Site‐averaged GHG budgets were surprisingly variable (29.2 ± 17.4 t CO 2 ‐eq. ha −1 yr −1 ) and partially higher than all published data and the IPCC default emission factors for GHG inventories. Generally, CO 2 (27.7 ± 17.3 t CO 2 ha −1 yr −1 ) dominated the GHG budget. Nitrous oxide (2.3 ± 2.4 kg N 2 O‐N ha −1 yr −1 ) and methane emissions (30.8 ± 69.8 kg CH 4 ‐C ha −1 yr −1 ) were lower than expected except for CH 4 emissions from nutrient‐poor acidic sites. At single peatlands, CO 2 emissions clearly increased with deeper mean water table depth ( WTD ), but there was no general dependency of CO 2 on WTD for the complete data set. Thus, regionalization of CO 2 emissions by WTD only will remain uncertain. WTD dynamics explained some of the differences between peatlands as sites which became very dry during summer showed lower emissions. We introduced the aerated nitrogen stock (N air ) as a variable combining soil nitrogen stocks with WTD . CO 2 increased with N air across peatlands. Soils with comparatively low SOC concentrations showed as high CO 2 emissions as true peat soils because N air was similar. N 2 O emissions were controlled by the WTD dynamics and the nitrogen content of the topsoil. CH 4 emissions can be well described by WTD and ponding duration during summer. Our results can help both to improve GHG emission reporting and to prioritize and plan emission reduction measures for peat and similar soils at different scales.

The ecology of multiple colour defences - Tim Caro; Tom N. Sherratt; Martin Stevens (Evolutionary Ecology, 2016)

Two- and three-dimensional co-culture models of soft tissue healing: pericyte-endothelial cell interaction - Martina Jennewein; Monika Bubel; Silke Guthörl; Wolfgang Metzger; Martin Weigert; Tim Pohlemann; Martin Oberringer (Cell and Tissue Research, 2016)

Risk-based approach to developing a national residue sampling plan for testing under European Union regulation for veterinary medicinal products and coccidiostat feed additives in domestic animal production - Martin Danaher; Conor Shanahan; Francis Butler; Rhodri Evans; Dan O’Sullivan; Denise Glynn; Tim Camon; Peadar Lawlor; Michael O’Keeffe (Food Additives & Contaminants: Part A, 2016)

Rates of CO2 efflux and changes in DOC concentration resulting from the addition of POC to the fluvial system in peatlands - Claire S. Goulsbra; Martin G. Evans; Tim E. H. Allott (Aquatic Sciences, 2016)

Sporadic hotspots for physico-chemical retention of aquatic organic carbon: from peatland headwater source to sea - Sheila M. Palmer; Chris D. Evans; Pippa J. Chapman; Annette Burden; Tim G. Jones; Tim E. H. Allott; Martin G. Evans; Catherine S. Moody; Fred Worrall; Joseph Holden (Aquatic Sciences, 2016)

Paths to a sustainable food sector: integrated design and LCA of future food supply chains: the case of pork production in Sweden - Ulf Gunnar Sonesson; Katarina Lorentzon; Annica Andersson; Ulla-Karin Barr; Jan Bertilsson; Elisabeth Borch; Carl Brunius; Margareta Emanuelsson; Leif Göransson; Stefan Gunnarsson; Lars Hamberg; Anna Hessle; et al. (The International Journal of Life Cycle Assessment, 2016)

Dimmuborgir: a rootless shield complex in northern Iceland - Alasdair Skelton; Erik Sturkell; Martin Jakobsson; Draupnir Einarsson; Elin Tollefsen; Tim Orr (Bulletin of Volcanology, 2016)

Exome sequencing identifies a nonsense mutation in Fam46a associated with bone abnormalities in a new mouse model for skeletal dysplasia - Susanne Diener; Sieglinde Bayer; Sibylle Sabrautzki; Thomas Wieland; Birgit Mentrup; Gerhard K. H. Przemeck; Birgit Rathkolb; Elisabeth Graf; Wolfgang Hans; Helmut Fuchs; Marion Horsch; Thomas Schwarzmayr; et al. (Mammalian Genome, 2016)

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis - Isabel Spier; Martin Kerick; Dmitriy Drichel; Sukanya Horpaopan; Janine Altmüller; Andreas Laner; Stefanie Holzapfel; Sophia Peters; Ronja Adam; Bixiao Zhao; Tim Becker; Richard P. Lifton; et al. (Familial Cancer, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Sustainability spaces for complex agri-food systems - Stephen Whitfield; Tim G. Benton; Martin Dallimer; Les G. Firbank; Guy M. Poppy; Susannah M. Sallu; Lindsay C. Stringer (Food Security, 2015)

Response of endothelial cells and pericytes to hypoxia and erythropoietin in a co-culture assay dedicated to soft tissue repair - Gerrit Schneider; Monika Bubel; Tim Pohlemann; Martin Oberringer (Molecular and Cellular Biochemistry, 2015)

Harmonia + and Pandora +: risk screening tools for potentially invasive plants, animals and their pathogens - Bram D’hondt; Sonia Vanderhoeven; Sophie Roelandt; François Mayer; Veerle Versteirt; Tim Adriaens; Els Ducheyne; Gilles San Martin; Jean-Claude Grégoire; Iris Stiers; Sophie Quoilin; Julien Cigar; et al. (Biological Invasions, 2015)

Comparative 3D microanatomy and histology of the eyes and central nervous systems in coleoid cephalopod hatchlings - Elvira Wild; Tim Wollesen; Gerhard Haszprunar; Martin Heß (Organisms Diversity & Evolution, 2015)

Development of a microtiter plate-based assay for the detection of lipase-catalyzed transesterifications in organic solvents - Martin Pöhnlein; Tim Finkbeiner; Christoph Syldatk; Rudolf Hausmann (Biotechnology Letters, 2015)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

The US Navy Coupled Ocean-Wave Prediction System - Richard Allard; Erick Rogers; Paul Martin; Tommy Jensen; Philip Chu; Tim Campbell; James Dykes; Travis Smith; Jeikook Choi; Uriah Gravois (Oceanography, 2014)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Breeding for value in a changing world: past achievements and future prospects - Tim White; John Davis; Salvador Gezan; Jiri Hulcr; Eric Jokela; Matias Kirst; Timothy A. Martin; Gary Peter; Greg Powell; Jason Smith (New Forests, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Mammography utilization among Black and White Medicare beneficiaries in high breast cancer mortality US counties - Mandeep K. Virk-Baker; Michelle Y. Martin; Robert S. Levine; Xin Wang; Tim R. Nagy; Maria Pisu (Cancer Causes & Control, 2013)

Integrating multiple lines of evidence to better understand the evolutionary divergence of humpback dolphins along their entire distribution range: a new dolphin species in Australian waters? - Martin Mendez; Thomas A. Jefferson; Sergios‐Orestis Kolokotronis; Michael Krützen; Guido J. Parra; Tim Collins; Giana Minton; Robert Baldwin; Per Berggren; Anna Särnblad; Omar A. Amir; Vic M. Peddemors; et al. (Molecular Ecology, 2013)
The conservation of humpback dolphins, distributed in coastal waters of the Indo‐West Pacific and eastern Atlantic Oceans, has been hindered by a lack of understanding about the number of species in the genus ( Sousa ) and their population structure. To address this issue, we present a combined analysis of genetic and morphologic data collected from beach‐cast, remote‐biopsied and museum specimens from throughout the known Sousa range. We extracted genetic sequence data from 235 samples from extant populations and explored the mitochondrial control region and four nuclear introns through phylogenetic, population‐level and population aggregation frameworks. In addition, 180 cranial specimens from the same geographical regions allowed comparisons of 24 morphological characters through multivariate analyses. The genetic and morphological data showed significant and concordant patterns of geographical segregation, which are typical for the kind of demographic isolation displayed by species units, across the Sousa genus distribution range. Based on our combined genetic and morphological analyses, there is convincing evidence for at least four species within the genus ( S. teuszii in the Atlantic off West Africa, S. plumbea in the central and western Indian Ocean, S. chinensis in the eastern Indian and West Pacific Oceans, and a new as‐yet‐unnamed species off northern Australia).

Bromelain down-regulates myofibroblast differentiation in an in vitro wound healing assay - Kathrin Aichele; Monika Bubel; Gunther Deubel; Tim Pohlemann; Martin Oberringer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

New insight into the structure of RNA in red clover necrotic mosaic virus and the role of divalent cations revealed by small-angle neutron scattering - Stanton L. Martin; Lilin He; Flora Meilleur; Richard H. Guenther; Tim L. Sit; Steven A. Lommel; William T. Heller (Archives of Virology, 2013)

Eight-phase alkali feldspars: low-temperature cryptoperthite, peristerite and multiple replacement reactions in the Klokken intrusion - Ian Parsons; John D. Fitz Gerald; Matthew T. Heizler; Lynn L. Heizler; Tim Ivanic; Martin R. Lee (Contributions to Mineralogy and Petrology, 2013)

Minimizing nitrate leaching while maintaining crop yields: insights by simulating net N mineralization - Sabine Heumann; Annegret Fier; Martin Haßdenteufel; Heinrich Höper; Walter Schäfer; Tim Eiler; Jürgen Böttcher (Nutrient Cycling in Agroecosystems, 2013)

Prey preferences of bushmeat hunters in an East African savannah ecosystem - Andimile Martin; Tim Caro; Christian Kiffner (European Journal of Wildlife Research, 2013)

Acute anxiety increases the magnitude of the cold shock response before and after habituation - Martin James Barwood; Jo Corbett; Richard Green; Tim Smith; Perry Tomlin; Lydia Weir-Blankenstein; Michael J. Tipton (European Journal of Applied Physiology, 2013)

Soft tissue fibroblasts from well healing and chronic human wounds show different rates of myofibroblasts in vitro - Florian Schwarz; Martina Jennewein; Monika Bubel; Joerg H. Holstein; Tim Pohlemann; Martin Oberringer (Molecular Biology Reports, 2013)

Identification of RARRES1 as a core regulator in liver fibrosis - Andreas Teufel; Diana Becker; Susanne N. Weber; Steven Dooley; Katja Breitkopf-Heinlein; Thorsten Maass; Katrin Hochrath; Markus Krupp; Jens U. Marquardt; Martin Kolb; Bernhard Korn; Christof Niehrs; et al. (Journal of Molecular Medicine, 2012)

Simulation of carbon pool changes in woodlots in eastern Zambia using the CO2FIX model - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2012)

Functional investigation of β-adrenoceptors in human isolated detrusor focusing on the novel selective β3-adrenoceptor agonist KUC-7322 - Yasuhiko Igawa; Tim Schneider; Yoshinobu Yamazaki; Satoshi Tatemichi; Yukio Homma; Osamu Nishizawa; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Einsatz der Quelltermmethode bei Hochwasserschutzkonzeptionen im ländlichen Raum - Carsten Lange; Reinhard Hinkelmann; Martin Lindenberg; Tim Fröhlich (WASSERWIRTSCHAFT, 2012)

Cortisol and finfish welfare - Tim Ellis; Hijran Yavuzcan Yildiz; Jose López-Olmeda; Maria Teresa Spedicato; Lluis Tort; Øyvind Øverli; Catarina I. M. Martins (Fish Physiology and Biochemistry, 2012)

Differential Transcript Expression of Wall-loosening Candidates in Leaves of Maize Cultivars Differing in Salt Resistance - Christoph-Martin Geilfus; Christian Zörb; Christina Neuhaus; Tim Hansen; Hartwig Lüthen; Karl H. Mühling (Journal of Plant Growth Regulation, 2011)

A meta-analysis of severity and yield loss from ascochyta blight on field pea in Western Australia - Moin U. Salam; William J. MacLeod; Tim Maling; Ian Prichard; Mark Seymour; Martin J. Barbetti (Australasian Plant Pathology, 2011)

Development and characterization of a Chinese hamster ovary cell-specific oligonucleotide microarray - Mark Melville; Padraig Doolan; William Mounts; Niall Barron; Louane Hann; Mark Leonard; Martin Clynes; Tim Charlebois (Biotechnology Letters, 2011)

Impact of climate change in relation to ascochyta blight on field pea in Western Australia - Moin U. Salam; William J. MacLeod; Kawsar P. Salam; Tim Maling; Martin J. Barbetti (Australasian Plant Pathology, 2011)

Effects of two different dosing regimens of terlipressin on organ functions in ovine endotoxemia - Matthias Lange; Christian Ertmer; Sebastian Rehberg; Andrea Morelli; Gabriele Köhler; Tim G. Kampmeier; Hugo Van Aken; Martin Westphal (Inflammation Research, 2011)

Influence of putative exopolysaccharide genes on Pseudomonas putida KT2440 biofilm stability - Martin Nilsson; Wen‐Chi Chiang; Mustafa Fazli; Morten Gjermansen; Michael Givskov; Tim Tolker‐Nielsen (Environmental Microbiology, 2011)
Summary We report a study of the role of putative exopolysaccharide gene clusters in the formation and stability of Pseudomonas putida KT2440 biofilm. Two novel putative exopolysaccharide gene clusters, pea and peb , were identified, and evidence is provided that they encode products that stabilize P. putida KT2440 biofilm. The gene clusters alg and bcs , which code for proteins mediating alginate and cellulose biosynthesis, were found to play minor roles in P. putida KT2440 biofilm formation and stability under the conditions tested. A P. putida KT2440 derivative devoid of any identifiable exopolysaccharide genes was found to form biofilm with a structure similar to wild‐type biofilm, but with a stability lower than that of wild‐type biofilm. Based on our data, we suggest that the formation of structured P. putida KT2440 biofilm can occur in the absence of exopolysaccharides; however, exopolysaccharides play a role as structural stabilizers.

Erythropoietin ameliorates the reduced migration of human fibroblasts during in vitro hypoxia - Stephanie Breit; Monika Bubel; Tim Pohlemann; Martin Oberringer (Journal of Physiology and Biochemistry, 2011)

Epibacterial community patterns on marine macroalgae are host‐specific but temporally variable - Tim Lachnit; Diana Meske; Martin Wahl; Tilmann Harder; Ruth Schmitz (Environmental Microbiology, 2011)
Summary Marine macroalgae are constantly exposed to epibacterial colonizers. The epiphytic bacterial patterns and their temporal and spatial variability on host algae are poorly understood. To investigate the interaction between marine macroalgae and epiphytic bacteria, this study tested if the composition of epibacterial communities on different macroalgae was specific and persisted under varying biotic and abiotic environmental conditions over a 2‐year observation time frame. Epibacterial communities on the co‐occurring macroalgae Fucus vesiculosus, Gracilaria vermiculophylla and Ulva intestinalis were repeatedly sampled in summer and winter of 2007 and 2008. The epibacterial community composition was analysed by denaturing gradient gel electrophoresis (DGGE) and 16S rRNA gene libraries. Epibacterial community profiles did not only differ significantly at each sampling interval among algal species, but also showed consistent seasonal differences on each algal species at a bacterial phylum level. These compositional patterns re‐occurred at the same season of two consecutive years. Within replicates of the same algal species, the composition of bacterial phyla was subject to shifts at the bacterial species level, both within the same season but at different years and between different seasons. However, 7–16% of sequences were identified as species specific to the host alga. These findings demonstrate that marine macroalgae harbour species‐specific and temporally adapted epiphytic bacterial biofilms on their surfaces. Since several algal host‐specific bacteria were highly similar to other bacteria known to either avoid subsequent colonization by eukaryotic larvae or to exhibit potent antibacterial activities, algal host‐specific bacterial associations are expected to play an important role for marine macroalgae.

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Epstein-Barr virus-associated pneumonia and bronchiolitis obliterans syndrome in a lung transplant recipient - Andi Krumbholz; Tim Sandhaus; Angela Göhlert; Albert Heim; Roland Zell; Renate Egerer; Martin Breuer; Eberhard Straube; Peter Wutzler; Andreas Sauerbrei (Medical Microbiology and Immunology, 2010)

Allometric models for estimation of aboveground carbon stocks in improved fallows in eastern Zambia - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2010)

Isolated thallus-associated compounds from the macroalga Fucus vesiculosus mediate bacterial surface colonization in the field similar to that on the natural alga - Tim Lachnit; Martin Wahl; Tilmann Harder (Biofouling, 2010)

Anatomy of a low temperature zircon outgrowth - Duncan C. Hay; Tim J. Dempster; Martin R. Lee; David J. Brown (Contributions to Mineralogy and Petrology, 2010)

The clinical value of neutrophil extracellular traps - Tim Lögters; Stefan Margraf; Jens Altrichter; Jindrich Cinatl; Steffen Mitzner; Joachim Windolf; Martin Scholz (Medical Microbiology and Immunology, 2009)

Serving GODAE Data and Products to the Ocean Community - Jon Blower; Frederique Blanc; Mike Clancy; Peter Cornillon; Craig Donlon; Peter Hacker; Keith Haines; Steve Hankin; Thomas Loubrieu; Sylvie Pouliquen; Martin Price; Tim Pugh; et al. (Oceanography, 2009)

Carbon pools in tree biomass and the soil in improved fallows in eastern Zambia - Martin L. Kaonga; Tim P. Bayliss-Smith (Agroforestry Systems, 2009)

Computational object recognition: a biologically motivated approach - Tim C. Kietzmann; Sascha Lange; Martin Riedmiller (Biological Cybernetics, 2009)

The effect of different warming methods on sensory nerve conduction velocity in shipyard workers occupationally exposed to hand–arm vibration - Martin Cherniack; Anthony J. Brammer; Ronnie Lundstrom; Tim F. Morse; Greg Neely; Tohr Nilsson; Donald Peterson; Esko Toppila; Nicholas Warren; Ulysses Diva; Marc Croteau; Jeffrey Dussetschleger (International Archives of Occupational and Environmental Health, 2008)

Syndromes from segmental vibration and nerve entrapment: observations on case definitions for carpal tunnel syndrome - Martin Cherniack; Anthony J. Brammer; Ronnie Lundstrom; Tim F. Morse; Greg Neely; Tohr Nilsson; Donald Peterson; Esko Toppila; Nicholas Warren; Ulysses Diva; Marc Croteau; Jeffrey Dussetschleger (International Archives of Occupational and Environmental Health, 2008)

In vitro wounding: effects of hypoxia and transforming growth factor β1 on proliferation, migration and myofibroblastic differentiation in an endothelial cell-fibroblast co-culture model - Martin Oberringer; Claudia Meins; Monika Bubel; Tim Pohlemann (Journal of Molecular Histology, 2008)

Invasion history, habitat preferences and phenology of the invasive ladybird Harmonia axyridis in Belgium - Tim Adriaens; Gilles San Martin y Gomez; Dirk Maes (BioControl, 2008)

Predicting the future carbon budget of an upland peat catchment - Fred Worrall; Tim Burt; John Adamson; Mark Reed; Jeff Warburton; Alona Armstrong; Martin Evans (Climatic Change, 2007)

The rate of senescence in maternal performance increases with early‐life fecundity in red deer - Daniel H. Nussey; Loeske E. B. Kruuk; Alison Donald; Martin Fowlie; Tim H. Clutton‐Brock (Ecology Letters, 2006)
Tradeoffs between reproduction and somatic maintenance are a frequently cited explanation for reproductive senescence in long‐lived vertebrates. Between‐individual variation in quality makes such tradeoffs difficult to detect and evidence for their presence from wild populations remains scarce. Here, we examine the factors affecting rates of senescence in maternal breeding performance in a natural population of red deer ( Cervus elaphus ), using a mixed model framework to control for between‐individual variance. Senescence began at 9 years of age in two maternal performance traits. In both traits, females that produced more offspring in early life had faster rates of senescence. This tradeoff is evident alongside significant effects of individual quality on late life breeding performance. These results present rare evidence in support of the disposable soma and antagonistic pleiotropy theories of senescence from a wild vertebrate population and highlight the utility of mixed models for testing theories of ageing.

European phenological response to climate change matches the warming pattern - ANNETTE MENZEL; TIM H. SPARKS; NICOLE ESTRELLA; ELISABETH KOCH; ANTO AASA; REIN AHAS; KERSTIN ALM‐KÜBLER; PETER BISSOLLI; OL'GA BRASLAVSKÁ; AGRITA BRIEDE; FRANK M. CHMIELEWSKI; ZALIKA CREPINSEK; et al. (Global Change Biology, 2006)
Global climate change impacts can already be tracked in many physical and biological systems; in particular, terrestrial ecosystems provide a consistent picture of observed changes. One of the preferred indicators is phenology, the science of natural recurring events, as their recorded dates provide a high‐temporal resolution of ongoing changes. Thus, numerous analyses have demonstrated an earlier onset of spring events for mid and higher latitudes and a lengthening of the growing season. However, published single‐site or single‐species studies are particularly open to suspicion of being biased towards predominantly reporting climate change‐induced impacts. No comprehensive study or meta‐analysis has so far examined the possible lack of evidence for changes or shifts at sites where no temperature change is observed. We used an enormous systematic phenological network data set of more than 125 000 observational series of 542 plant and 19 animal species in 21 European countries (1971–2000). Our results showed that 78% of all leafing, flowering and fruiting records advanced (30% significantly) and only 3% were significantly delayed, whereas the signal of leaf colouring/fall is ambiguous. We conclude that previously published results of phenological changes were not biased by reporting or publication predisposition: the average advance of spring/summer was 2.5 days decade −1 in Europe. Our analysis of 254 mean national time series undoubtedly demonstrates that species' phenology is responsive to temperature of the preceding months (mean advance of spring/summer by 2.5 days°C −1 , delay of leaf colouring and fall by 1.0 day°C −1 ). The pattern of observed change in spring efficiently matches measured national warming across 19 European countries (correlation coefficient r =−0.69, P

Effects of gender, age and hypertension on β-adrenergic receptor function in rat urinary bladder - Elfaridah P. Frazier; Tim Schneider; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Quantitative assessment of DNA methylation: potential applications for disease diagnosis, classification, and prognosis in clinical settings - Romulo Martin Brena; Tim Hui-Ming Huang; Christoph Plass (Journal of Molecular Medicine, 2006)

Effects of ageing on muscarinic receptor subtypes and function in rat urinary bladder - Tim Schneider; Peter Hein; Martina B. Michel-Reher; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Different cell cycle responses of wound healing protagonists to transient in vitro hypoxia - Martin Oberringer; Martina Jennewein; Sandra E. Motsch; Tim Pohlemann; Andreas Seekamp (Histochemistry and Cell Biology, 2005)

Digital Forestry: A White Paper - Guang Zhao; Guofan Shao; Keith M. Reynolds; Michael C. Wimberly; Tim Warner; John W. Moser; Keith Rennolls; Steen Magnussen; Michael Köhl; Hans-Erik Anderson; Guillermo A. Mendoza; Limin Dai; et al. (Journal of Forestry, 2005)
Digital Forestry has been proposed as ”the science, technology, and art of systematically acquiring, integrating, analyzing, and applying digital information to support sustainable forests.” Although rooted in traditional forestry disciplines, Digital Forestry draws from a host of other fields that, in the past few decades, have become important for implementing the concept of forest ecosystem management and the principle of sustainable forestry. Digital Forestry is a framework that links all facets of forestry information at local, national, and global levels through an organized digital network. It is anticipated that a new set of principles will be established when practicing Digital Forestry concept for the evolution of forestry education, research, and practices as the 21st century unfolds.

Does climate at different scales influence the phenology and phenotype of the River Warbler Locustella fluviatilis? - Pavel Kaňuščák; Martin Hromada; Piotr Tryjanowski; Tim Sparks (Oecologia, 2004)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Chirp sub-bottom profiler source signature design and field testing - Martin Gutowski; Jon Bull; Tim Henstock; Justin Dix; Peter Hogarth; Tim Leighton; Paul White (Marine Geophysical Research, 2002)

Modeling Northern Peatland Decomposition and Peat Accumulation - Steve Frolking; Nigel T. Roulet; Tim R. Moore; Pierre J. H. Richard; Martin Lavoie; Serge D. Muller (Ecosystems, 2001)

Guidelines for consistent reporting of exchanges/to nature within life cycle inventories (LCI) - Roland Hischier; Martin Baitz; Rolf Bretz; Rolf Frischknecht; Niels Jungbluth; Torsten Marheineke; Phil McKeown; Michiel Oele; Philippe Osset; Isa Renner; Tim Skone; Helena Wessman; et al. (The International Journal of Life Cycle Assessment, 2001)

Activation of tomato PR and wound-related genes by a mutagenized tomato MAP kinase kinase through divergent pathways - Tim Xing; Kamal Malik; Teresa Martin; Brian L Miki (Plant Molecular Biology, 2001)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Interactions between coot (Fulica atra) and submerged macrophytes: the role of birds in the restoration process - Martin R. Perrow; J. Hans Schutten; John R. Howes; Tim Holzer; F. Jane Madgwick; Adrian J. D. Jowitt (Hydrobiologia, 1997)